(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2017)
Since its inception in 1992, Nollywood, the Nigerian film industry, has grown into a transnational cinema and the second largest film industry in the world thanks in large part to the popularity of the highly affective and dramatic narrative conventions the industry has perfected. In the last decade, Nollywood filmmakers have produced films that depict the African immigrant lived experience in American cities like New York City, Chicago, Los Angeles, and Atlanta. These films are glocal in nature; while set in the United States and featuring African characters, the films combine both local and global settings, cultural attitudes, identity politics, and the protean nature of everyday life in America. By examining the films Anchor Baby and Baby Oku in America, this article analyses how Nollywood filmmakers employ the industry’s affective and melodramatic narrative practices to show African immigrant characters’ complex emotional, epistemological, and phenomenological responses to both the urban spaces they inhabit and the African spaces they left behind.